Challenges of Developing a Logistics Hub Case Study: Batu Ampar Port - Petrus Haryanto Wibowo; Al Husni (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2021)
Batam as a region with leading sectors of marine, tourism, industry, fisheries and Batu Ampar as Main Port has the potential to be developed. One of the main centers of activity is large ports and international airports that have the potential to become national and international-scale economic gateways for logistics hubs. The aim of this research was to determine The Challenges of developing a logstics hub in Batu Ampar Port. This research uses descriptive qualitative approach and secondary data from the Batam port office and the Human Settlements and Spatial Planning Office. The results of this research are there are some challenges from the aspects of Geography, Infrastructure, Connectivity, Transportation costs and time, Trade movement requirements, Shipping dependability, Transport and trade regulations. Poor logistics performance is a major obstacle to trade growth in most cities in Indonesia. In this case there is an international shipping port but does not yet have adequate facilities and infrastructure to become a logistics hub.